Kardiochirurgia dorosłych Endoscopic radial artery harvesting as a material in coronary artery bypass grafting in 15 patients - Hrapkowicz, Tomasz; Bisleri, Gianluigi; Wojarski, Jacek; Nożyński, Jacek; Farmas, Arkadiusz; Styn, Tomasz; Zych, Bartłomiej; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
The minimally invasive radial artery harvesting is widely used in cardiac surgery. This harvesting method should include injury limitation and appropriate graft quality. Aim: The aim of the study was the assessment of usefulness of endoscopic radial harvesting with acknowledgment of bypass flow parameters and clinical results. Material and Methods: In April 2006, the endoscopic radial harvesting was used in 15 patients during coronary artery bypass grafting operations. During the procedures flow measurements in grafts were performed. Assessments of clinical data as well as forearm wound healing were carried out. Results: All endoscopically harvested radial artery has been implemented during coronary artery bypass grafting. Any wall damage was observed. Doppler flow measurements have shown in all cases correct parameters. In the postoperative observation, no complications were observed. Moreover, there were neither forearm neurological nor wound healing problems. Conclusions: The endoscopic radial harvesting technique is a safe method, it allows to harvest a correct material to coronary artery bypass grafting and simultaneously assures a very beneficial cosmetic result.